Participação da via WNT/B-catenina na inflamação e na nocicepção da artrite crônica experimental da articulação temporomandibular - Sousa, Luane Macêdo (2021)
Rheumatoid arthritis (RA) is a chronic, progressive and a systemic inflammatory disease, and studies show that the temporomandibular joint (TMJ) is usually involved. The Wnt canonical signaling pathway participates in many inflammatory conditions. However, this pathway also plays an essential role in neuronal development, synaptic establishment and strengthening, and neuroplasticity. The purpose of this study was to evaluate the participation of the Wnt/b-catenin signaling pathway in the TMJ and along the trigeminal pathway in arthritic rats. For this, Wistar rats were divided into 2 groups (n=6): RA and Saline Groups. Arthritis induction was performed through 3 weekly intra-articular injections (i.a.; 10μl/joint) of methylated bovine serum albumin (mBSA) in the left TMJ. The Saline group received saline solution in the left TMJ (i.a.; 10μl/joint). It were evaluated: nociceptive threshold, inflammatory infiltrate, birefringence of collagen fibers, immunohistochemistry for IL-1b, TNF-a, IL-6, RANKL, NFκB, Wnt-10b, b-catenin, DKK1, c-Myc and cyclin D1 from articular cartilage and synovial membrane, immunofluorescence analysis for c-Fos, Wnt-10b and b-catenin in the trigeminal ganglion and trigeminal spinal tract. The RA group showed intense inflammatory infiltrate and synovial membrane hyperplasia, joint destruction, proliferation of type III collagen fibers, increased immunoexpression of pro- inflammatory cytokines and Wnt-10b, b-catenin, RANKL, NFκB and cyclin D1 in articular cartilage and c-Myc in the synovial membrane (p < 0.05). It was observed a decrease in the nociceptive threshold and a high expression of Wnt-10b and b-catenin only in the trigeminal ganglion, and c-Fos expression were observed peripheral and central tissues in arthritic rats (p<0.05). These results suggest that the Wnt/b-catenin pathway participates in TMJ structural damage and is involved in peripheral painful sensitization in arthritic rats.